2016
DOI: 10.17706/ijbbb.2016.6.3.75-83
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Determination and Assessment of Cyanosis

Abstract: Cyanosis can be detected in a blue-purplish discoloration area commonly around the mucous membranes which are around the lips, fingers and toes. It is one of the respiratory distress' symptoms in newborn babies that can be caused by either the low level of oxygenated blood or poor circulation. Low oxygen saturation in the blood will make the skin and lips appear to be blue since the blood's color changes from bright red to a darker bluish. Babies with cyanosis need urgent assessment and initiation of medical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Cyanosis assessment in a newborn is highly abstract and the evaluation of cyanosis is challenging because of many aspects such as the environment's lighting colour and the intensity level and the effect of the coloured objects in the surrounding [13]. An observer model and the light propagation's series represented by the transfer functions in the block diagrams described a cyanosis occurrence in optical properties in skin layers of human was obtained and discussed as in Figure 2 and Figure 3 in the study of Azmi et al [14]. The study demonstrated three different output lights which explained the light paths in humans' skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanosis assessment in a newborn is highly abstract and the evaluation of cyanosis is challenging because of many aspects such as the environment's lighting colour and the intensity level and the effect of the coloured objects in the surrounding [13]. An observer model and the light propagation's series represented by the transfer functions in the block diagrams described a cyanosis occurrence in optical properties in skin layers of human was obtained and discussed as in Figure 2 and Figure 3 in the study of Azmi et al [14]. The study demonstrated three different output lights which explained the light paths in humans' skin.…”
Section: Introductionmentioning
confidence: 99%
“…Fatihah et al [16] had set up the experiment using the cyanosis observation lamp, the Philips Master LEDspot LED light (940 type lamp; Philips) as the ❒ ISSN: 2502-4752 source of the illuminant to measure the cyanosis colour values of their developed cyanosis manikin as the employed observation lamp was suggested the most suitable lamp to be used in the operating theater to assess cyanosis. While the cyanosis quantification in [14] is mostly based on the assumption and simplification, the details about the transmission spectra of HbO 2 and Hb has not been extinsively investigated. Therefore, this paper aims to add the detailing of the transfer functions as an additional approach for cyanosis quantification and determination in International Commission on Illumination (CIE) L * a * b * colour values based on the HbO 2 and Hb's actual reflectance spectrum.…”
Section: Introductionmentioning
confidence: 99%